The Cassava Mealybug, Phenacoccus sp. in the Republic of Zaire - Nwanze, K.F.; Leuchner, K.; Ezumah, H.C. (1979)
The occurrence of the cassava mealybug Phenacoccus sp. in Zaire is reported. Data on its biology, particularly oviposition, female fecundity and nymphal development are presented. Most of the insects settle on the leaf midrib and secondary veins and the growing points of cassava. The first instar nymph (crawler) is vary important in the spread and survival of the species, the latter being within dormant leaf buds during the wet season. Dispersal is by movement of infested planting material (passive) and airborne populations of crawlers (active). Treatment of cuttings with an appropriate insecticide before planting, manipulation of planting time and soil moisture conservation may aid in reducing damage to the crop. The occurrence of Spalgis lemolea Druce, a predator of the pest is also reported.